LABORATORY EXERCISE TO DETERMINE CONTRAST IN LASER MARKING OF ARTICLES - Lazov, Lyubomir; Teirumnieks, Edmunds; Teirumnieka, Erika; Cacivkin, Pavel; Angelov, Nikolay; Karadzhov, Tsanko (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The laser marking has been established in recent years as one of the modern innovative methods for marking many industrial products. The report examines a new laboratory exercise for the subject Laser Technology, studied in some technical universities. A new approach is proposed to determine the contrast of the laser marking process. Described is the purpose and the main tasks as well as the new skills and knowledge that students can exercise through this laboratory exercise. Students implement a test matrix consisting of squares of a certain size using the raster marking method. Through the new laboratory exercise, students can explore and analyze the dependencies of the contrast of laser markings on different dimensions influencing the technological process. The capabilities of the new approach allow learners to become more familiar with the factors that influence the modern process of laser marking widely used in modern industry. The results of the experiments the students summarize using a new modern digital approach to analyze the contrast against the background of the marked surface. From the experimental graphical dependencies of the variation of the power and speed contrast, they draw conclusions about the optimal process parameters.